Assessing the Health and Economic Outcomes of a 9-Valent HPV Vaccination Program in the United Kingdom - Kwame Owusu-Edusei; Cody Palmer; Olga Ovcinnikova; Giampiero Favato; Vincent Daniels (Journal of Health Economics and Outcomes Research)
**Background:** The United Kingdom (UK) switched from using the 4-valent human papillomavirus (HPV) vaccine (Gardasil®) to the 9-valent vaccine (Gardasil 9®) in 2021.